Analysis of Accounting Technology Utilization in Advancing Micro, Small and Medium Enterprises (MSMEs) in Medan City - Nasir, Miftah Farid; Ginting, Berupilihen Br (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This study aims to analyze the application of digital accounting in Micro, Small and Medium Enterprises (MSMEs) and the impact it has on financial management, operational efficiency, and business competitiveness. Along with the development of information technology, many MSMEs have begun to switch to digital accounting systems to improve the efficiency, accuracy, and transparency of financial reports. However, the implementation of this digital system is not free from challenges, such as limited financial and human resources, and lack of technical knowledge in operating accounting software. This research uses a qualitative approach by collecting data through interviews, observations, and documentation studies on a number of MSMEs that have and have not adopted digital accounting. The results show that the implementation of digital accounting has a positive impact in the form of increased efficiency in cash flow management, reduced recording errors, and faster and more accurate financial reporting. In addition, MSMEs that adopt this technology tend to have stronger competitiveness in the market because they can provide more transparent and reliable reports to third parties, such as investors and financial institutions. Nonetheless, there are challenges in implementing digital accounting, such as the high cost of software and training, and the inability of some MSMEs to access the necessary technological infrastructure. This study also recommends that the government and financial institutions provide support in the form of incentives and training programs to accelerate the adoption of digital accounting among MSMEs, so that they can be more competitive and sustainable in the long run.